Special Arrangement between the Government of the French Republic, the Government of the Kingdom of Belgium, the Government of the Kingdom of the Netherlands and the Government of the United Kingdom of Great Britain and Northern Ireland concerning Security Matters relating to Trains using the Channel Fixed Link, Brussels, 7 July 2020. ([2020-08-13]) - Unknown
No abstract available